Bulbophyllum section Macrocaulia (Orchidaceae) in Vietnam - Dang, Minh Quan; Averyanov, Leonid V.; Maisak, Tatiana V.; Tran, Thi Thuy Nhan; Nguyen, van Canh; Wook, Um Sung; Nguyen, Quoc Bao; Truong, Ba Vuong (Phytotaxa, 2024)
The paper presents an illustrated taxonomic survey of Bulbophyllum sect. Macrocaulia in the flora of Vietnam including a key to species identification, data on phenology, habitat, distribution and taxonomic notes for all accepted species. The estimated conservation status of these species in Vietnam is also discussed. Additionally, Bulbophyllum papilluliferum is described as a new species for science. The presence of B. ignevenosum in Vietnam is confirmed and documented correcting its long-standing misidentification as B. menghaiense or B. moniliforme.